My self as an other: on autoimmunity and "other" paradoxes. Issue 1 (10th June 2004) - Cohen, E
Abstract : The rubric autoimmunity currently encompasses sixty to seventy diverse illnesses which affect many of the tissues of the human body. Western medical practice asserts that the crisis known as autoimmune disease arises when a biological organism compromises its own integrity by misrecognising parts of itself as other than itself and then seeks to eliminate these unrecognised and hence antagonistic aspects of itself. That is, autoimmune illnesses seem to manifest the contradictory and sometimes deadly proposition that the "identity": body/self both is and is not "itself". Based on the assumption that under normal circumstances "the self" ought to coincide naturally with "the body"—or at the very least the self ought to inhabit the living location of the body more or less unproblematically—this scientific paradigm depicts autoimmune illness as a vital paradox. Yet for those of us who have lived through the experience of an autoimmune crisis, the living paradox that we embody may also lead us to question the basis upon which these medical assumptions rest. This essay raises some of these questions.